A pectic polysaccharide from peach palm fruits (Bactris gasipaes) and its fermentation profile by the human gut microbiota in vitro. (January 2017) - Cantu-Jungles, Thaisa Moro; Cipriani, Thales R.; Iacomini, Marcello; Hamaker, Bruce R.; Cordeiro, Lucimara M.C.
Abstract: Depending on their chemical structure, pectic polymers may be fermented by different bacteria in the human gut and, therefore, display a different metabolite profile. We aimed to investigate the chemical structure of pectins from peach palm fruits and to evaluate their in vitro fecal fermentation profiles. A fraction (PW-AP) containing a linear highly methyl esterified homogalacturonan (degree of esterification of 70%) with minor portions of xylogalacturonan and type I rhamnogalacturonan was submitted to fermentation by the human gut microbiota. It produced significantly less gas than fructooligosaccharides (FOS) at all evaluated time points, and in 24 h presented a cumulative gas production 27% lower than FOS. Drops in pH could be observed during fermentation of both FOS and PW-AP. Moreover, the pectin was slower fermented than FOS, though with a similar production of total short chain fatty acids (SCFA) and a lower production of branched chain fatty acids. The amounts of specific SCFA differed from that of FOS, with higher production of acetate (16.2%) and propionate (6.2%) and lower production butyrate (112%). The ratio of total SCFA production to gas production was 4.0 mL/µmol and 5.5 mL/µmol for FOS and PW-AP, respectively, indicating that the latter leads to less gas formation per µmol of produced SCFA. Overall, the understanding of how pectic structures are fermented brings new insights into the fiber utilization by the human gut microbiota and its relation to biological outcomes. Graphical abstract: Highlights: A pectic polyssacharide from peach palm pulp (PW-AP) was obtained and characterized. PW-AP was submitted to in in vitro fecal fermentation. Fermentation of PW-AP resulted in a similar production of total SCFAs than FOS. Compared to FOS, higher acetate and propionate and lower butyrate were produced. This paper brings new insights into fiber utilization by the human gut microbiota.